2016
DOI: 10.1080/02678373.2016.1163804
|View full text |Cite
|
Sign up to set email alerts
|

Stuck in a job: being “locked-in” or at risk of becoming locked-in at the workplace and well-being over time

Abstract: In this study, being “locked-in” at the workplace is conceptualized as being in a non-preferred workplace while at the same time perceiving low employability. The aim of the study was to investigate how being locked-in or at risk of becoming locked-in (being in a non-preferred workplace yet currently satisfied, combined with perceiving low employability) relates to well-being (subjective health and depressive symptoms). The hypotheses were tested in a Swedish longitudinal sample (T1 in 2010 and T2 in 2012) of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
103
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(112 citation statements)
references
References 49 publications
6
103
2
1
Order By: Relevance
“…29 Another attractive example is to incorporate walking breaks throughout the workday; 29 30 however, many companies cannot allow this because it interferes with workflow. 31 Innovative approaches are needed to help sedentary office workers move more.…”
Section: Discussionmentioning
confidence: 99%
“…29 Another attractive example is to incorporate walking breaks throughout the workday; 29 30 however, many companies cannot allow this because it interferes with workflow. 31 Innovative approaches are needed to help sedentary office workers move more.…”
Section: Discussionmentioning
confidence: 99%
“…Walking or standing while at work are 2 possible solutions for disrupting total workplace sitting time (Dempsey et al, 2016); however, these options are often not practical (Judice et al, 2015; Levin and Chisholm, 2016) because leaving a workstation or office can hinder workflow (Stengard et al, 2016). New methods are needed to help sedentary workers move more.…”
Section: Introductionmentioning
confidence: 99%
“…This situation causes to the individual to feel himself / herself in constant psychological pressure. Because, in general, it has been found that individuals who feel confined to their current job and have difficulty in finding new jobs, have lower levels of well-being (Stengard et al, 2016).…”
Section: Extensive Summarymentioning
confidence: 99%
“…There are studies claim that perceived employability is an effect on employee well-being (De Cuyper et al, 2008;Stengard et al, 2016;Lu, Sun ve Du 2016). The effect of the employee well-being on the intention to leave the job has also been revealed through various studies (Schultz et al, 2015: Stetz, Castro andBliese, 2007;Fisher and Hanna, 1931).…”
Section: Extensive Summarymentioning
confidence: 99%